PENGARUH PENGGUNAAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR PKN DISEKOLAH DASAR - syafrina, syafrina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study purpose to determine the effect influence of the use cooperative type Numbered Head Together to the civic education learning outcomes. This research is an experimental research design with Quasi Exsperimental. The sample in this research is class VA and class VB. The calculation result of research data used was obtained t t-test 2,26 > 1.67722 ttable at α level of 0.05. With it can be concluded that there is significant influence of the use cooperative tipe Numbered Head Together to the civic education learning outcomes of class V SDN 13 Cingkariang Kecamatan Banuhampu Kabupaten Agam. Key Word : Model NHT, Learning Outcomes of the civic education